Development and Validation of an RP-HPLC Method for CB13 Evaluation in Several PLGA Nanoparticle Systems - J. Álvarez-Fuentes; L. Martín-Banderas; I. Muñoz-Rubio; M. A. Holgado; M. Fernández-Arévalo (The Scientific World Journal)
A simple, fast, and reversed-phase high-performance liquid chromatographic (RP-HPLC) method has been developed and validated for determining of a cannabinoid derivate, which displays potent antihyperalgesic activity, 1-naphthalenyl[4-(pentyloxy)-1-naphthalenyl]methanone (CB13) into PLGA nanoparticles. Separation was achieved in a C18 column using a mobile phase consisting of two solvents: solvent A, consisting of acetonitrile : water : acetic acid (75 : 23.7 : 1.3 v/v), and solvent B, consisting of acetonitrile. An isocratic method (70 : 30 v/v), with a flow rate of 1.000 mL/min, and a diode array detector were used. The developed method was precise, accurate, and linear over the concentration range of analysis with a limit of detection and a limit of quantification of 0.5 and 1.25 μg/mL, respectively. The developed method was applied to the analysis of CB13 in nanoparticles samples obtained by three different procedures (SEV, FF, and NPP) in terms of encapsulation efficiency and drug release. Nanoparticles size and size distribution were also evaluated founding that NPP method presented the most lowest particle sizes with narrow-size distribution (≈320 nm) and slightly negative zeta potential (≈−25 mV) which presumes a suitable procedure for the synthesis of PLGA-CB13 nanoparticles for oral administration.